CFD Modeling of Turbulent Air Flow in Three Different Diffusers Used For Turbocharger Compressor - Chehhat, A.; Boulahrouz, S.; Aboudi, A.; Chermime, B.; Chahaoui, O. (University of Eloued جامعة الوادي, 2018)
This study is carried out to investigate by CFD modeling the three dimensional turbulent air flow through the centrifugal compressor used in turbocharger of diesel engines, the full compressor stage with vaned and vaneless diffusers is considered (i.e. From the impeller inlet to the volute outlet). A great attention has been attributed to the effect of the diffuser solidity. For this purpose, three diffusers have been considered (vaneless diffuser, conventional vaned diffuser, and low solidity vaned diffuser) in order to analyze their effect, especially on the turbulence intensity distribution, on the pressure loss, and on the compressor performance. To validate numerical model, a comparison with a similar tested turbocharger is made in case of vanless diffuser, and a good agreement is seen.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Centrifugal Compressor, Turbocharger, Turbulence, Compressible Flow